Enhancing tamarind quality and shelf-life through improved storage techniques - Marichamy , M S; Ponuswami , V; Saraswathy , S; Jyothsna J (Plant Science Today, 2024)
Tamarind (Tamarindus indica L.) is a versatile spice crop with economic significance, known for its diverse applications in pulp, seed and timber. Thriving in challenging conditions like poor soils and drought, it has become crucial in various uses, particularly in wastelands. In this post-harvest study, tamarind pods underwent deshelling, deseeding and defibering before applying treatments to extend the shelf life of the pulp. Five additives and four packaging materials, under 2 storage conditions, were tested in a factorial design. Results of over 6 months revealed that treating tamarind pulp with 0.2 % sulphur fumes, packed in aluminium foil, and stored refrigerated minimized browning and moisture content. This treatment also showed lower total carbohydrate, reducing sugar, protein, amino acid and total phenol content. Conversely, pulp treated with 2.0 % ascorbic acid, packed in palmyrah leaf bags and stored refrigerated exhibited higher acidity. Pulp treated with 0.2 % sulphur fumes, packed in palmyrah leaf bags and stored under ambience showed consistently higher total soluble solids. The findings suggest that treating pulp with 0.2 % sulphur fumes, using aluminium foil for packing and refrigerated storage can significantly reduce browning, making it an ideal choice for extended stability and potential export markets. Furthermore, adopting aluminium foil as a packing material in Indian conditions proves economically feasible, ensuring better pulp quality during prolonged storage, particularly for small-scale tamarind growers.